Learning Strategies Role in Developing Autonomous EFL Students - Ayaat Tamimi; Anwar Hussein-Abdel Razeq (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The current study investigated strategies that non-native English majors used in learning English.  In particular, the study aimed at finding the metacognitive learning strategies, cognitive learning strategies, affective learning strategies and socio-interactive learning strategies and tactics that 4th year English major university students used to help them become autonomous learners.  A sample of 40 participants was chosen randomly to participate in the study from a population of 100 students. Semi-structured interviews were used to collect the study data.  The thematic analysis qualitative method was used to analyze the collected data.   Results showed that the participants in the study do use a myriad of learning strategies.  However, their use needs major improvement.  Further, they are not aware of several effective learning strategies that they could tremendously benefit from. The authors present some pedagogical and classroom implications that could assist learners in improving their English proficiency and become autonomous learners.